Representasi Maskulinitas dalam Iklan - Kurnia, Novi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2004)
The phenomenon of hegemonic masculinity have been well understood, despite the fact that mass media in general and advertisement in particular, is a medium for contestation between masculinity and feminity. This article shows that, new feature of masculinity has come due to the adaptation of feminity. The new feature of masculinity has been known as metrosexual.